Lived Experiences of Patients with COVID-19 in the Kurdistan Region, Iraq: A Qualitative Study - Sarhang Qadir Ibrahim (Hawler Medical University, 2021)
Background and objective: COVID-19 has adverse effects on physical and mental health and threatens the quality of life significantly; therefore, it is necessary to help COVID-19 patients with their lifestyle, which is tightly bound to the quality of their lives. The present study aims to develop plans to improve the quality of life among COVID-19 patients by analyzing their lived experiences. Methods and patients: The present qualitative study was conducted from August to September 2020 on twelve COVID-19 patients hospitalized in Erbil's Emirates Hospital, the Kurdistan Region of Iraq. In-depth semi-structured interviews (12) were utilized to collect data. Trustworthiness was ensured by making an excellent prolonged relationship with the patients, peer-checking, member-checking, and implementing experts' suggestion at every stage. Four main themes were extracted from the interviews, which were transcribed verbatim and analyzed using the six methodological activities proposed by Van Manen. Results: The present study results indicated that COVID-19 patients have a difficult time dealing with the disease and getting adapted to their new situation, leading to a remarkable decrease in the quality of their lives. Analyzing the transcribed interviews led to emergence of four main themes: "disbelief in being really ill," "fear and stress," "changes in lifestyle," and "seriously adhering to health guidelines." Conclusion: Our results showed that COVID-19 patients suffer from physical pain and undergo poor mental health due to fear and stress resulting in worsening quality of life. A deep understanding of COVID-19 patients' states and situations is highly significant to help nurses and nursing managers plan effective strategies for caring for patients with COVID-19.